Is FAST stroke smart? Do the content and language used in awareness campaigns describe the experience of stroke symptoms? - Bray, Janet; O'Connell, B.; Gilligan, A.; Livingston, P.; Bladin, C. (Wiley-Blackwell Publishing Asia, 2010)
Background Public education campaigns for stroke are used worldwide. However, there are few published evaluations of such campaigns.Aim This cross-sectional study examined patient and bystander awareness of two Australian campaigns, 'FAST' (face, arm, speech, time) and 'Signs of Stroke', and evaluated the campaigns ability to identify stroke and to describe the symptom experience.Methods Interviews were conducted with either stroke patients or a key bystander for consecutive eligible cases admitted to two metropolitan hospitals between August 2006 and April 2008. Participants were asked to describe awareness of the FAST campaign, the symptoms experienced and to evaluate the symptom descriptions of Signs of Stroke against their own experience.Results A total of 100 patients and 70 bystanders were interviewed for 170 cases (71% of eligible cases). Only 12% of those interviewed were aware of the FAST campaign, and of these few (19%) were able to recall all FAST symptoms, with only one bystander using the FAST assessments to identify stroke. At least one FAST symptom was reported by 84% and one Signs of Stroke symptom by 100%. Less than half of those experiencing 'weakness or paralysis' thought this description exactly described their experience. Common descriptors of symptoms were: face or mouth droop or drop; trouble using, coordinating or moving arm, hand or leg; trouble walking or standing; numbness; and slurring or loss of speech.Conclusion Awareness of the FAST and Signs of Stroke campaigns was low, with poor recall and little use of the FAST assessments. Some symptom descriptions used in the campaign were not reflective of the symptom experience. The content and language of these campaigns could be improved to portray stroke symptoms more realistically. © 2010 The Authors. International Journal of Stroke © 2010 World Stroke Organization.